Comparison of vermiwash and vermicompost tea properties produced from different organic beds under greenhouse conditions - Mehdi Zarei; Vahid Alah Jahandideh Mahjen Abadi; Ameneh Moridi (International Journal of Recycling of Organic Waste in Agriculture)
Abstract Purpose Using different organic beds to produce vermicompost may influence on quality of vermicompost and its derived productions. Methods A greenhouse experiment was conducted to compare the properties of vermicompost, vermiwash and vermicompost tea obtained from three types of organic beds consisted of cow manure, leaf meal and a combination of cow manure and leaf meal (1:1 w/w). Results Cow manure vermicompost had more desirable effect on many measured traits toward leaf meal and combination of leaf meal and cow manure vermicomposts. Vermicompost tea obtained from three vermicompost types was richer in terms of macro and micro nutrients, C/N, percent of organic matter and organic carbon toward the vermiwash produced from the same vermicompost. Vermiwash and vermicompost tea produced from cow manure vermicompost were at first order in majority of measured traits toward others. Conclusions Generally vermicompost which was richer in nutrient concentrations affected intensively quality of vermiwash and vermicompost tea produced from it.